2001
DOI: 10.1038/sj.bjp.0704152
|View full text |Cite
|
Sign up to set email alerts
|

Agonists of proteinase‐activated receptor 1 induce plasma extravasation by a neurogenic mechanism

Abstract: 1 Thrombin, generated in the circulation during injury, cleaves proteinase-activated receptor 1 (PAR1) to stimulate plasma extravasation and granulocyte in®ltration. However, the mechanism of thrombin-induced in¯ammation in intact tissues is unknown. We hypothesized that thrombin cleaves PAR1 on sensory nerves to release substance P (SP), which interacts with the neurokinin 1 receptor (NK1R) on endothelial cells to cause plasma extravasation. 2 PAR1 was detected in small diameter neurons known to contain SP in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
125
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(129 citation statements)
references
References 44 publications
3
125
1
Order By: Relevance
“…These inflammatory effects are, at least in part, mediated by cleavage and activation of proteinase-activated receptors (PARs), 68,69 indicating that, in neurogenic inflammation, proteinases may activate PARs on sensory neurons to stimulate release of SP, which, in turn, additionally enhances the inflammatory response. Moreover, the release of other neuropeptides, eg, calcitonin gene related peptide (CGRP) may also be up-regulated on stress exposure with subsequent PAR activation (Kuhlmei A, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory effects are, at least in part, mediated by cleavage and activation of proteinase-activated receptors (PARs), 68,69 indicating that, in neurogenic inflammation, proteinases may activate PARs on sensory neurons to stimulate release of SP, which, in turn, additionally enhances the inflammatory response. Moreover, the release of other neuropeptides, eg, calcitonin gene related peptide (CGRP) may also be up-regulated on stress exposure with subsequent PAR activation (Kuhlmei A, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…37 Tryptase responses are modulated by proteinase-activated receptors (PAR) coupled to a G-protein. These receptors are present in bladder afferent neurons 38 and mediate plasma extravasation induced by tryptase and thrombin. 38 PA receptors are also present in normal human kidneys, 39 and mediate the response of human proximal tubular cells to thrombin.…”
Section: Par and Tryptasementioning
confidence: 99%
“…These receptors are present in bladder afferent neurons 38 and mediate plasma extravasation induced by tryptase and thrombin. 38 PA receptors are also present in normal human kidneys, 39 and mediate the response of human proximal tubular cells to thrombin. 39 Others have reported that activation of PAR induced detectable levels of IL-6 production in a dose-dependent fashion.…”
Section: Par and Tryptasementioning
confidence: 99%
“…In contrast, other studies have shown that PAR-1 activation can cause plasma extravasation in the stomach (De Garavilla et al 2001), suggestive of a pro-inflammatory effect of PAR-1. The difference may lie in the model used, with one being an assessment of the effect of PAR-1 activation on HClethanol-induced damage in the rat (Kawabata et al 2004) and one being an assessment of PAR-1 effects in normal mouse stomach (De Garavilla et al 2001). The stimulation of plasma exudation by PAR-1 activation in the mouse is dependent upon sensory afferent nerves.…”
Section: Effect Of Pars On Epithelial Functionmentioning
confidence: 47%
“…Related to this is the recognition that PAR-2 can mediate hyperalgesia of the intestine (Coelho et al 2002). Both of these situations point to a relationship between PAR-1 and capsaicin-sensitive afferent activation and indeed this relationship has been demonstrated experimentally , De Garavilla et al 2001. We have evidence that capsaicin-sensitive extrinsic sensory afferent neurons can, through local axon reflexes, stimulate chloride secretion in guinea pig ileum in vitro (Vanner & MacNaughton 1995).…”
Section: Effect Of Pars On Epithelial Functionmentioning
confidence: 80%